Faktor-Faktor yang Mempengaruhi Kejadian Stunting di Desa Sukowiryo Wilayah Kerja Puskesmas Jelbuk Kabupaten Jember - Puspita, Meila Putri; Keswara, Nila Widya (FAKULTAS ILMU KESEHATAN UNIVERSITAS MUHAMMADIYAH PAREPARE, 2026)
Stunting is a chronic nutritional problem that has a long-term impact on children's growth and development, and is a priority for health programmes in Indonesia. Sukowiryo Village, which is part of the Jelbuk Community Health Centre's working area in Jember Regency, still has cases of stunting among toddlers, which are thought to be influenced by multidimensional factors such as maternal education, family income, exclusive breastfeeding, the quality of complementary foods, history of infection, and environmental sanitation conditions. This study aims to identify the factors that influence the incidence of stunting and determine the dominant factors in Sukowiryo Village. The study uses an observational analytical design with a cross-sectional approach. The study population consists of all toddlers aged 24–59 months residing in the village, and the sample was determined through total sampling of 30 toddlers. The dependent variable was the incidence of stunting. The independent variables included maternal education, family income, exclusive breastfeeding, quality of complementary foods, history of infection, and environmental sanitation. Data were collected through questionnaires, anthropometric measurements, and verification of maternal and child health (MCH) cards. Analysis was performed using the Chi-Square test for bivariate relationships and logistic regression for multivariate analysis. The results of the study indicate that maternal education, family income, exclusive breastfeeding, quality of complementary feeding, history of infection, and environmental sanitation are significantly associated with stunting (p